Post-cyclone agroforestry is helping to solve food insecurity in Vanuatu - Kampai, Jessie (Technical Centre for Agricultural and Rural Cooperation, 2018)
In the wake of Cyclone Pam, Live & Learn Vanuatu set about ending food insecurity in some of the country’s worst affected communities. Seedlings, reared in nurseries, replaced the crops that were washed away in the disaster. The implementation of agroforestry plots, plant tissue grafting, and the introduction of carrots and broccoli to the islands are being hailed as important steps forward in the fight to end food insecurity.